Pengendalian Diri Dan Konflik Dalam Penggunaan Instagram - Hisna Daniati, Nur; Firman; Netrawati (CV. ITTC INDONESIA, 2024)
This research examines how an individual's level of self-control can influence their behavior on Instagram, as well as how this behavior contributes to the emergence of conflict, both with themselves and with others. The research method used is a qualitative approach with in-depth interviews and observations involving students from various backgrounds. Research results show that individuals with high self-control tend to experience less conflict, both in social and emotional contexts. Conversely, a lack of self-control can cause tension in interpersonal relationships and negatively impact mental well-being. It is hoped that these results will help mental health practitioners and Instagram users understand the dynamics of social media use and the importance of self-control.